Growth and Yield Response of Superior Rice Varieties under Different Biofertilizer Rates in Lowland Rice Fields - Purwanto, Oky Dwi; Nugraha, Dedi; Patriyawaty, Nia Romania; Wardana, I Putu (Department of Agronomy and Horticulture, IPB University, 2025)
Efforts to increase rice productivity through a sustainable and environmentally friendly approach are using biofertilizers. The biofertilizer contains beneficial microorganisms that play an essential role in promoting plant growth and increasing rice yield. This study aimed to investigate the potential of biofertilizers and evaluate the performance of superior rice varieties by applying several rates of biofertilizers in lowland rice fields for enhancing growth and yield. A split-plot design was laid out using a randomized complete block design with three replications. The main plot consisted of superior rice varieties, including “Inpari 30”, “Inpari 32”, “Inpari 36”, and “Inpari 42”, while the subplot involved biofertilizer rates of 0, 400, and 800 g.ha-1. The utilization of biofertilizer contributed to the improvement of seedling height and root length. Applying biofertilizer increased plant height, panicle length, the number of grains per panicle, the number of filled grains per panicle, and the percentage of f illed grains, while decreasing the number of unfilled grains per panicle. The application of biofertilizer at a rate of 400 g.ha-1 significantly improved grain yields for “Inpari 30”, “Inpari 32”, and “Inpari 36”. However, “Inpari 42” required a higher biofertilizer rate of 800 g.ha-1 to produce high grain yields. The grain yield of superior rice varieties increased by 10%-21.6% with the application of biofertilizer. The findings of this study may provide recommendations for applying biofertilizers to enhance grain yields of several superior rice varieties in specific lowland rice field agroecosystems.